Answer: y = [tex]\frac{-4}{3}[/tex]x + [tex]\frac{5}{3}[/tex]
Step-by-step explanation:
First we will find the slope, then we will find the y-intercept.
Slope is change in y over change in x:
[tex]\frac{-1-3}{2--1}=\frac{-4}{3}[/tex]
Now we will solve for the y-intercept:
y = [tex]\frac{-4}{3}[/tex]x + b
(-1) = [tex]\frac{-4}{3}[/tex](2) + b
-1 = [tex]\frac{-8}{3}[/tex] + b
[tex]\frac{5}{3}[/tex] = b
b = [tex]\frac{5}{3}[/tex]
Final equation:
y = [tex]\frac{-4}{3}[/tex]x + [tex]\frac{5}{3}[/tex]